Encouragement of Active Learning Strategies in Mathematics Courses as an Effort to Improve Students' Critical Thinking Skills - Erpin Evendi (IKIP Mataram, 2022)
The current study aims to implement active learning strategies in mathematics courses as an effort to improve students' critical thinking (CT) skills. The randomized pretest-posttest control design was employed to evaluate the efficacy of the active learning strategy intervention, as opposed to expository teaching. The CT skills measured before and after the intervention in each group included indicators: analysis skills (AS), inference skills (IS), evaluation skills (ES), and decision-making skills (DMS). Essay test instruments were developed, validated, and employed to measure CT. Learning interventions with active and expository learning strategies have been analyzed and compared based on indicator (CTi) and individual (CTs) parameters. The results of the study show the advantages of active learning strategies when compared to expository teaching in terms of improving students' CT skills on all CTi indicators. Accompanying the results on CTi, test results based on CTs parameters lead to active learning strategy interventions in mathematics courses that have a significant impact on improving students' CT skills. The information obtained from the results of the current study can provide benefits in the future development of students' CT skills, and has broad implications for many future literature and studies.